2021
DOI: 10.3390/ijms22157830
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Studies of Mitochondrial Malate: Quinone Oxidoreductase from Toxoplasma gondii

Abstract: Toxoplasma gondii is a protozoan parasite that causes toxoplasmosis and infects almost one-third of the global human population. A lack of effective drugs and vaccines and the emergence of drug resistant parasites highlight the need for the development of new drugs. The mitochondrial electron transport chain (ETC) is an essential pathway for energy metabolism and the survival of T. gondii. In apicomplexan parasites, malate:quinone oxidoreductase (MQO) is a monotopic membrane protein belonging to the ETC and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(27 citation statements)
references
References 94 publications
1
25
1
Order By: Relevance
“…These α values suggest that the two inhibitors had the potential to bind to both free CjMQO as well as CjMQO/substrates complex with slightly high preference for free CjMQO in case of inhibitor versus malate. Although this mechanism is consistent with previously reported inhibition mechanisms for ferulenol on TgMQO (Acharjee et al, 2021), it contrasts with the inhibition mechanism reported for PfMQO (Hartuti et al, 2018). The noncompetitive and mixed-type of inhibition suggest that 1) the concentration of the substrate does not influence the binding capacity of the two inhibitors, and 2) they 3) and using graphical methods (Supplementary Figures 12, 13), further supports that embelin and ferulenol were noncompetitive inhibitors versus quinone and mixed-type versus malate.…”
Section: Mechanism Of C Jejuni Mqo Inhibition By Ferulenol and Embelinsupporting
confidence: 93%
See 2 more Smart Citations
“…These α values suggest that the two inhibitors had the potential to bind to both free CjMQO as well as CjMQO/substrates complex with slightly high preference for free CjMQO in case of inhibitor versus malate. Although this mechanism is consistent with previously reported inhibition mechanisms for ferulenol on TgMQO (Acharjee et al, 2021), it contrasts with the inhibition mechanism reported for PfMQO (Hartuti et al, 2018). The noncompetitive and mixed-type of inhibition suggest that 1) the concentration of the substrate does not influence the binding capacity of the two inhibitors, and 2) they 3) and using graphical methods (Supplementary Figures 12, 13), further supports that embelin and ferulenol were noncompetitive inhibitors versus quinone and mixed-type versus malate.…”
Section: Mechanism Of C Jejuni Mqo Inhibition By Ferulenol and Embelinsupporting
confidence: 93%
“…The optimal temperature for the activity of the purified CjMQO was 40 °C; however, the enzyme retained 60% and 93% of its maximal activity at ambient (25 °C) and human body (37 °C) temperatures, respectively (Figure 2A). This optimal temperature was lower than values published for MQOs from T. gondii (50 °C), thermophilic (Ohshima and Tanaka, 1993;Kabashima et al, 2013;Acharjee et al, 2021). It was superior to the temperature reported for P. taetrolens MQO (30 °C) and P. falciparum MQO (37 °C) (Hartuti et al, 2018;Oh et al, 2020).…”
Section: Optimization Of C Jejuni Mqo Activity Assay Conditionscontrasting
confidence: 56%
See 1 more Smart Citation
“…MQO, found in many bacteria and single-celled eukaryotes, catalyzes the conversion of malate to oxaloacetate as part of the TCA cycle. While MQO catalyzes this conversion in an irreversible reaction and reduces CoQ, the canonical mammalian malate dehydrogenase (MDH) catalyzes the same reaction reversibly and ultimately reduces NAD+ (Acharjee et al, 2021). T. gondii also expresses MDH and localization studies found that MQO and MDH both localize to the mitochondrion (Fleige et al, 2008).…”
Section: Colo S Sa L Com Pl E X E S Of T H E E L Ect Ron T R a Nsport...mentioning
confidence: 99%
“…Furthermore, a study revealed that these molecules also target dihydroorotate dehydrogenase (DHODH) and it is likely that the simultaneous inhibition of NDH2 and DHODH by HDQs impairs parasite growth (Hegewald et al, 2013). Finally, a recently published study demonstrated that the apicomplexan MQO, a mitochondrial enzyme with no orthologues in mammals, could represent a potential drug target (Acharjee et al, 2021). In T. gondii, MQO activity can be inhibited with ferulenol, and in P. falciparum inhibition is more pronounced in combination with atovaquone (Hartuti et al, 2018).…”
Section: Bu L L Sey E : T H E M I Toc Hon Dr Ion a S A Drug Ta Rgetmentioning
confidence: 99%